Disability, Gender and Hiring Discrimination: A Field Experiment - Vegar Bjørnshagen; Dan-Olof Rooth; Elisabeth Ugreninov (Institute of Labor Economics (IZA), 2023)
This article examines disability discrimination in the hiring process and explores variation in how the intersection of disability and gender shapes employers' hiring behavior by occupational context and gender segregation. We use data from a field experiment in which approximately 2,000 job applications with randomly assigned information about disability were sent to Swedish employers with vacancies. We find that nondisabled applicants receive 33 percent more callbacks than similarly qualified wheelchair users despite applying for jobs where the impairment should not interfere with performance. The results indicate no heterogeneity in levels of disability discrimination against men and women on average across occupations or by occupational gender segregation. However, levels of discrimination differ considerably among occupations, varying from no evidence of disability discrimination to discrimination against both disabled men and disabled women as well as cases where disability discrimination is found only against women or only against men. The results thus indicate that disability and gender interact and shape discrimination in distinct ways within particular contexts, which we relate to intersectional stereotyping and norms of gender equality influencing hiring practices but not to declared ambitions for diversity or gender equality legislation.
Keywords: I14; J14; J23; J64; J71; 330; disability; hiring discrimination; gender; field experiment; correspondence study